Reinvestigating the Sexual Violence "Justice Gap" in the Swedish Criminal Justice System: Victim-Centered Alternatives to the Criminal Trial. (January 2023) - Carroll, Caitlin P.
The high rate of attrition in the processing of sexual violence cases within the criminal justice system has been framed as a "justice gap, " an institutional failure to get justice for victim-survivors. In this article, I analyze the processing of rape cases in the Swedish criminal justice system, one with a particularly high attrition rate. Drawing upon interviews with criminal justice professionals, I illuminate the inadequacy of the justice gap as a measure of victim-centered justice. Through policy reforms, the Swedish criminal justice system has instituted victim-centered practices that offer victim-survivors alternative forms of justice without increasing the prosecution rate.